The role of TBX2 and the anti-cancer activity of chromomycin A5 in pancreatic ductal adenocarcinoma - Bai, Jinming (Department of Human Biology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies, with a dismal 5-year survival rate of 13%. Current treatments show limited efficacy due to late diagnosis and therapy resistance, highlighting an urgent need for novel therapeutic strategies. The T-box transcription factor, TBX2, is significantly overexpressed in PDAC tissues and correlates with poor prognosis and distant metastasis, suggesting its potential as a therapeutic target. Recently, Chromomycin A5 (CA5), a marine-derived compound, was identified as a TBX2-specific inhibitor with demonstrated anticancer effects in several cancer types. However, its efficacy in PDAC and the specific molecular mechanisms remains unexplored. This study aimed to: (1) elucidate the role of TBX2 in PDAC progression and its potential as a therapeutic target, and (2) evaluate the anticancer activity and underlying molecular mechanisms of CA5 in PDAC. Initial screening for TBX2 expression over four PDAC cell lines identified SW1990 cells as high TBX2-expressing cells suitable for the functional studies. Both SW1990 and CFPAC-1 metastatic PDAC cells were ideal for drug evaluation studies. TBX2's function was assessed in SW1990 cells through siRNA-mediated knockdown followed by cell counting for proliferation analysis, wound healing assays for migration assessment, and western blot analysis of cell cycle regulators and EMT markers. CA5's anticancer activity was evaluated in both cell lines using 2D and 3D culture models (MTT cytotoxicity assays, colony formation assays, Matrigel transwell invasion assays, wound healing assays, and spheroid formation with Calcein-AM/propidium iodide viability staining), with gemcitabine serving as a reference drug. Molecular mechanisms of CA5 were investigated through fluorescence spectroscopy for DNA binding, immunofluorescence and western blot detection of γH2AX for DNA damage XII assessment, flow cytometry for cell cycle and Annexin V-FITC/PI apoptosis analyses, western blot analysis of apoptotic pathway proteins, and qRT-PCR examination of TBX2 and its downstream targets. The relationship between TBX2 expression and CA5 efficacy was further explored using doxycycline-inducible TBX2-overexpressing SW1990 cell lines established through the PiggyBac transposon system. The study revealed that while TBX2 knockdown in SW1990 cells had minimal impact on cell proliferation, it significantly impaired cell migration through an EMT independent mechanism. In both SW1990 and CFPAC-1 cells, CA5 demonstrated potent and selective anticancer activity in 2D and 3D models. Mechanistically, CA5 exhibited strong DNA-binding capabilities, as evidenced by fluorescence quenching and emission peak shifts. These DNA-binding properties increased γH2AX levels in both cell lines, triggering S-phase and G2/M cell cycle arrests in SW1990 cells and predominantly S-phase arrest in CFPAC-1 cells. CA5 activated primarily the intrinsic apoptotic pathway in SW1990 cells while engaging both intrinsic and extrinsic pathways in CFPAC-1 cells. Furthermore, CA5 reduced TBX2 protein levels in both cell lines and relieved its potential downstream tumour suppressors p21 and NDRG1. This study demonstrated that TBX2 promotes PDAC cell migration through an EMT independent mechanism, establishing its role in PDAC metastasis. Additionally, CA5 exhibits promising anticancer activity in PDAC cells through multiple mechanisms, including DNA damage induction and TBX2 inhibition, supporting its potential as a novel therapeutic agent for PDAC treatment.